KEANEKARAGAMAN JENIS IKAN DI KAWASAN MANGROVE SUNGAI KAKAP KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Asan, Stefanus Anton; Anwari, M Sofwan; Rifanjani, Slamet; Darwati, Herlina (Universitas Tanjungpura, 2019)
Forest mangrove constitute some ecosystem estuaria with system that apoplectic terbuka open and amenable nutrition pretty material organic and non organic along sediment from circle terrestrial. Literally ecology forest mangrove have a role urgent inside guard awkwaedness live water the sea and coastal. Literally economical, some research show that mangrove gives contributions to fish resources revolved 30%-44,18% the mangrove region a habitat for the various of fish, even some types of fish do breeding in the mangrove area. This research is aimed at exploring the diversity in the river mangrove area kakap district Kubu RayaÂ Province Borneo. Methods that used inside research here that is perposive sampling using tools catch nets and dragnet with 10 supprssant on broads 50 meter and installation draget at any dot observations. Samples taken in the show 6 points of observation within 100 meters. The setting of the sample points was done in the labyrinth p the mangrove orest, which is fine, moderate and badly demaged. Observations in the mangrove conditions affect the diversity of fish such as fine, moderate, and degraded conditions, the result is evidenced by accounts based on the reddish diersity in each observation station on this study is found as many as 5 different fish.Keyword : Fish, Mangrove, Species Diversity Of Fish